Photobiomodulation Therapy at 808 nm Does Not Improve Biceps Brachii Performance to Exhaustion and Delayed-Onset Muscle Soreness in Young Adult Women: A Randomized, Controlled, Crossover Trial - Azuma, Ricardo Henrique Esquivel; Merlo, Jeanne Karlette; Jacinto, Jeferson Lucas; Borim, Jayne Maria; da Silva, Rubens Alexandre; Pacagnelli, Francis Lopes; Nunes, Joao Pedro; Ribeiro, Alex Silva; Aguiar, Andreo Fernando (Frontiers in Physiology, 2021)
Objective: This study aims to investigate the effects of laser photobiomodulation (PBM) at 808 nm on biceps brachii performance to exhaustion, rating of perceived exertion (RPE), and delayed onset muscle soreness (DOMS) in untrained young women. Methods: Thirteen young women (20.1 ± 2.9 y) participated in a crossover study in which they received, in a counterbalanced manner, active and placebo laser PBM on two occasions (T1 and T2), separated by a 7-day washout period. During T1 and T2, participants received active (100 mW output power, irradiance of 35.7 W.cm-2, and total energy of 28 J per arm) or placebo laser irradiation on the biceps brachii muscle at 20 min. before the repetitions-to-failure test (6 sets at 60% of one-repetition maximum [1RM] until failure) for elbow flexion exercise. Number of repetitions performed and rating of perceived exertion (RPE) over the 6 sets, as well as DOMS from basal up to 72 h after the repetitions-to-failure test, were recorded. Results: There was a significant (time p < 0.05) reduction in the number of repetitions performed and an increase in RPE over 6 sets, with no statistical differences between placebo and active laser conditions (treatment x time p > 0.05). DOMS increased at 24 h post-exercise and progressively returned to baseline after 72 h in both conditions (time p < 0.05; treatment x time p > 0.05). Conclusion: Our results indicate that acute laser PBM at 808 nm does not improve biceps brachii performance to exhaustion, RPE, and DOMS in untrained women.